2012
DOI: 10.1037/a0028701
|View full text |Cite
|
Sign up to set email alerts
|

Behavior modification after inactivation of cerebellar dentate nuclei.

Abstract: Effort-based decision making occurs when subjects are given a choice between a reward available at a high response cost and a reward available at a low response cost and is altered in individuals with disorders such as autism or particular patterns of brain injury. The current study explored the relationship between effort-based decision making and reinforcement characteristics in the T maze. This was done using both normal animals and animals with bilateral inactivation of the cerebellar dentate nuclei. Rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 74 publications
1
11
1
Order By: Relevance
“…[39] Two days of training occurred prior to surgery to establish a pre-injury baseline on the rotarod. Animals were placed on the rotating cylinder against the rotation and the latency to fall was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…[39] Two days of training occurred prior to surgery to establish a pre-injury baseline on the rotarod. Animals were placed on the rotating cylinder against the rotation and the latency to fall was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…It is well known, however, that disruption of afferents to the cerebellum results in deficits in the acquisition of classical eyeblink conditioning and causes extinction of eyeblink conditioning in well trained animals (McCormick et al, 1985; McCormick, 2005). Most recently it has been reported that temporary, bilateral inactivation of the cerebellar dentate nuclei reduced operant responding for a food reward (Peterson et al, 2012). These studies are therefore consistent with the idea that the cerebellum potentially may play an important role in human reward processing.…”
Section: Evidence That Cerebellum Is Involved In Autism and Asdmentioning
confidence: 99%
“…However, behaviors outside of the motor domain have been shown to depend on an intact cerebellum, such as those involved in behavioral modification (Peterson et al, 2012). Furthermore, individuals with cerebellar lesions exhibit what has been termed cerebellar cognitive affective syndrome which is characterized by impaired executive functions, disrupted spatial cognition, blunted affect, inappropriate behavior, and language deficits (Schmahmann & Sherman, 1998).…”
Section: Asd Models Involving the Cerebellummentioning
confidence: 99%